2018
DOI: 10.1016/j.nmd.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

ECEL1 gene related contractural syndrome: Long-term follow-up and update on clinical and pathological aspects

Abstract: Autosomal recessive mutations in the ECEL1 gene have recently been associated with a wide phenotypic spectrum including severe congenital contractural syndromes and distal arthrogryposis type 5D (DA5D). Here, we describe four novel families with ECEL1 gene mutations, reporting 15 years of follow-up for four patients and detailed muscle pathological description for three individuals. In particular, we observed mild myopathic features, prominent core-like areas in one individual, and presence of nCAM positive fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 23 publications
6
16
0
Order By: Relevance
“…Moreover, respiratory issues reported earlier were also observed in our affected individuals (9, 19). Some of the features such as deep central groove in the tongue, digital webbing, spine issue and cleft palate reported by Ullmann et al (9), were not observed in our patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, respiratory issues reported earlier were also observed in our affected individuals (9, 19). Some of the features such as deep central groove in the tongue, digital webbing, spine issue and cleft palate reported by Ullmann et al (9), were not observed in our patients.…”
Section: Discussionsupporting
confidence: 87%
“…Phenotypes such as ptosis, distinct facial features, severe hand camptodactyly, toe and foot contractures, and knee deformities reported earlier (3, 1618) were also observed in the present affected individuals. While, Shaheen et al (19) reported incomitant strabismus in three affected individuals and Ullmann et al (9) reported the same feature in 1/7 affected individuals, this feature was also observed in both the affected individuals reported here. Moreover, respiratory issues reported earlier were also observed in our affected individuals (9, 19).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Clinical features include congenital distal joint contractures, fissured tongue, scoliosis and eye abnormalities, that is, ptosis and astigmatism 2. The characteristic fingers appearance help to identify the disorder and the underlying neurological aetiology 3…”
mentioning
confidence: 99%
“…Orthopaedic treatment options should be considered early and include tendon release, lengthening of the extensor tendon, correction of deformities, and supportive rehabilitation 4 5. A periodic assessment of the strength of upper and lower limbs is needed to monitor muscular weakening over time 3. Paediatricians should consider DA5D in children with a family history of clino-camptodactyly and articular retraction.…”
mentioning
confidence: 99%